Phenotypic features in MECP2 duplication syndrome: Effects of age. Issue 2 (10th November 2020) - Peters, Sarika U.; Fu, Cary; Marsh, Eric D.; Benke, Tim A.; Suter, Bernard; Skinner, Steve A.; Lieberman, David N.; Standridge, Shannon; Jones, Mary; Beisang, Arthur; Feyma, Timothy; Heydeman, Peter; et al.
Abstract: Background: MECP2 Duplication syndrome (MDS) is a rare X‐linked genomic disorder that is caused by interstitial chromosomal duplications at Xq28 encompassing the MECP2 gene. Although phenotypic features in MDS have been described, there is a limited understanding of the range of severity of these features, and how they evolve with age. Methods: The cross‐sectional results of N = 69 participants (ages 6 months‐33 years) enrolled in a natural history study of MDS are presented. Clinical severity was assessed using a clinician‐report measure as well as a parent‐report measure. Data was also gathered related to the top 3 concerns of parents as selected from the most salient symptoms related to MDS. The Child Health Questionnaire was also utilized to obtain parental reports of each child's quality of life to establish disease burden. Results: The results of linear regression from the clinician‐reported measure show that overall clinical severity scores, motor dysfunction, and functional skills are significantly worse with increasing age. Top concerns rated by parents included lack of effective communication, abnormal walking/balance issues, constipation, and seizures. Higher levels of clinical severity were also related to lower physical health quality of life scores as reported by parents. Conclusions: The data suggest that increasing levels of clinical severity are noted with older age, and this is primarily attributable to motor dysfunction, and functional skills. The results provide an important foundation for creating an MDS‐specific severity scale highlighting the most important domains to target for treatment trials and will help clinicians and researchers define clinically meaningful changes.